Structural and functional characteristics of the tripartite ABC transporter - Okada, Ui; Murakami, Satoshi (Microbiology (Reading, England), 2022)
ATP-binding cassette (ABC) transporters are one of the largest protein superfamilies and are found in all living organisms. These transporters use the energy from ATP binding and hydrolysis to transport various substrates. In this review, we focus on the structural and functional aspects of ABC transporters, with special emphasis on type VII ABC transporters, a newly defined class possessing characteristic structures. A notable feature of type VII ABC transporters is that they assemble into tripartite complexes that span both the inner and outer membranes of Gram-negative bacteria. One of the original type VII ABC transporters, which possesses all characteristic features of this class, is the macrolide efflux transporter MacB. Recent structural analyses of MacB and homologue proteins revealed the unique mechanisms of substrate translocation by type VII ABC transporters.